2012
DOI: 10.1186/1423-0127-19-4
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum stress mediating downregulated StAR and 3-beta-HSD and low plasma testosterone caused by hypoxia is attenuated by CPU86017-RS and nifedipine

Abstract: BackgroundHypoxia exposure initiates low serum testosterone levels that could be attributed to downregulated androgen biosynthesizing genes such as StAR (steroidogenic acute regulatory protein) and 3-beta-HSD (3-beta-hydroxysteroid dehydrogenase) in the testis. It was hypothesized that these abnormalities in the testis by hypoxia are associated with oxidative stress and an increase in chaperones of endoplasmic reticulum stress (ER stress) and ER stress could be modulated by a reduction in calcium influx. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
26
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 36 publications
5
26
0
Order By: Relevance
“…Degenerative changes in germ cells in aging rat showed oxidative stress and ER stress signaling pathway play important role [47,48]. Two independent study provide evidence that hypoxia downregulate androgen biosynthesizing genes such as steroidogenic acute regulatory protein (StAR) and 3-β-hydroxysteroid dehydrogenase (3β-HSD) in testis of rat by increasing calcium influx, oxidative stress and upregulation of ER stress signaling molecule Grp78, PERK and CHOP [49,50].…”
Section: Involvement Of Endoplasmic Reticulum Stress In Testis and Gementioning
confidence: 99%
“…Degenerative changes in germ cells in aging rat showed oxidative stress and ER stress signaling pathway play important role [47,48]. Two independent study provide evidence that hypoxia downregulate androgen biosynthesizing genes such as steroidogenic acute regulatory protein (StAR) and 3-β-hydroxysteroid dehydrogenase (3β-HSD) in testis of rat by increasing calcium influx, oxidative stress and upregulation of ER stress signaling molecule Grp78, PERK and CHOP [49,50].…”
Section: Involvement Of Endoplasmic Reticulum Stress In Testis and Gementioning
confidence: 99%
“…Madrid et al in 2013 reported that high-altitude hypoxia induced plasmatic and testicular testosterone decreased from the 5th day [5]. Liu et al reported in 2012 that in hypoxic rats, serum testosterone levels decreased and mRNA and protein expressions of testosterone biosynthesis related genes downregulated [23]. In this study, we determined the hypoxia effects on testosterone in Balb/c mouse serum and primary Leydig cells.…”
Section: Discussionmentioning
confidence: 97%
“…Liu et al reported in 2012 that in hypoxic rats, expression StAR and 3β-HSD were downregulated [23]. Su et al reported that increases in plasma leptin inhibited the expression of StAR and steroidogenic enzymes and attenuate adrenal responsiveness in hypoxic fetuses [30].…”
Section: Discussionmentioning
confidence: 99%
“…In humans and models of animal have found that hypoxic environment induces alterations of the male fertility, including low sperm counts, sperm mobility, plasma testosterone, and changes in testosterone levels (Farias et al, 2008;Pelliccione et al, 2011;Liu et al, 2012;Verratti and Giulio, 2012). An interesting thing to note is that spermatocyte apoptosis is the key in hypoxia-induced spermatogenic failure (Reyes et al, 2012b).…”
Section: Discussionmentioning
confidence: 99%